Don't Burn the Books, Read Them!. (1st August 2018) - Watson, Amanda
Abstract: Why do we still have books? To answer this question with views based not on the market trend, nor on the popular feeling that print is outdated and irrelevant, but on the American Bar Association's stated mission of Law Libraries to provide resources that enable legal education, 1 this article reviews the potential benefits and determents of different types of legal sources using both print and online formats and discusses whether external pressures should outweigh these factors dependent on the audience.